2006
DOI: 10.1080/01676830600674627
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Classification of Anterior Skull Base Anatomy Prior to Performing Medial Orbital Wall Decompression

Abstract: Keros classification provides an objective assessment of anterior skull base anatomy and can therefore guide the surgeon on the superior extent of medial wall bone removal during orbital decompression. This may help improve the safety profile of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 3 publications
1
15
0
1
Order By: Relevance
“…[7,9,10,25] The area of the entry of AEA through the lateral lamella into the olfactory fossa is considered the thinnest and at risk of injury causing CSF leak. [7][8][9] In our study we have observed that low or flattened contour of ethmoidal fovea as well as asymmetries between the sides in respect to height and contour of ethmoidal fovea were most commonly associated with Keros type I.…”
Section: Discussionmentioning
confidence: 99%
“…[7,9,10,25] The area of the entry of AEA through the lateral lamella into the olfactory fossa is considered the thinnest and at risk of injury causing CSF leak. [7][8][9] In our study we have observed that low or flattened contour of ethmoidal fovea as well as asymmetries between the sides in respect to height and contour of ethmoidal fovea were most commonly associated with Keros type I.…”
Section: Discussionmentioning
confidence: 99%
“…Gauba et al ascertained the prevalence of Keros types 1, 2 and 3 as 34%, 28% and 38%, respectively. [28] Adeel et al, however, give the corresponding values as 29.8%, 48.7% and 21.4%. [29] The lamina cribrosa had an average depth of 5.35mm in their study.…”
Section: Discussionmentioning
confidence: 95%
“…5C). 8,26 Although present in only approximately 1% of the population, recognition of this anatomic variant is crucial; a sinus surgeon may want to be much more conservative in cases with this skull base configuration. Preoperative CT evaluation should note any asymmetry in Keros configuration between the 2 skull base sides because this may also lead to complications when not recognized.…”
Section: Neurologic and Intracranial Complicationsmentioning
confidence: 99%